Forming term "strategic consulting" in context of scientific approaches - Oleg Klenin (Cхід, 2016)
In the article was analyzed term "consulting" using different scientific approaches and was presented authorial view to its maintenance. It was proved that modern changes of enterprises functioning needed to be laid by strategy as control system of development. It was found out that development of enterprises was possible in conditions of effective innovations usage, rates of increasing were connected with the level of strategic management. Was formed authorial position concerning term "strategic consulting" as professional activity in the system of strategic enterprise management. It was set that strategic consulting was powerful source of informative and intellectual resources for increasing level of competitiveness and innovative development. From the point of view scientific approaches it is suggested to present full term of "strategic consulting" as combination system and processing approaches with features of innovativeness that in future will to assist realization of strategic aims and targets of enterprise-customer.